The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2018
DOI: 10.1161/circresaha.118.313956
|View full text |Cite
|
Sign up to set email alerts
|

S -Nitrosoglutathione Reductase Is Essential for Protecting the Female Heart From Ischemia-Reperfusion Injury

Abstract: Rationale: Protein S-nitros(yl)ation (SNO) has been implicated as an essential mediator of nitric oxide-dependent cardioprotection. Compared to males, female hearts exhibit higher baseline levels of protein SNO and associated with this, reduced susceptibility to myocardial ischemia-reperfusion (I/R) injury. Female hearts also exhibit enhanced S-nitrosoglutathione reductase (GSNO-R) activity, which would typically favor decreased SNO levels as GSNO-R mediates SNO catabolism. Objective: Since female hearts exh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(24 citation statements)
references
References 62 publications
1
22
1
Order By: Relevance
“…We are the first to report the interaction of TMAO with gender in human heart failure myocardium, which has important implications when considering that this microbiome-derived metabolite has been reported widely as a mediator of atherosclerosis, platelet activation, and myocardial infarction [27][28][29]65 ; our data suggests it may be a contributor to the divergence in heart failure outcomes in men and women. An interaction of nitric oxide deficiency with gender in recovery post ischaemia has been reported before in mice 66 , and S-nitrosoglutathione reductase was reported to be a critical sex-dependent mediator of myocardial protein Snitrosylation in mice 67 and murine ex vivo hearts 68 (more active in females); S-nitrosylation is reported as an essential mediator of nitric oxide-dependent cardioprotection 67 . Other work in mice revealed that nitroglycerin-induced calcitonin generelated peptide release is eNOS-dependent, with a greater response in females 69 , and estrogen has been shown to upregulate NOS in neonatal rat cardiomyocytes 70 .…”
Section: Discussionmentioning
confidence: 78%
“…We are the first to report the interaction of TMAO with gender in human heart failure myocardium, which has important implications when considering that this microbiome-derived metabolite has been reported widely as a mediator of atherosclerosis, platelet activation, and myocardial infarction [27][28][29]65 ; our data suggests it may be a contributor to the divergence in heart failure outcomes in men and women. An interaction of nitric oxide deficiency with gender in recovery post ischaemia has been reported before in mice 66 , and S-nitrosoglutathione reductase was reported to be a critical sex-dependent mediator of myocardial protein Snitrosylation in mice 67 and murine ex vivo hearts 68 (more active in females); S-nitrosylation is reported as an essential mediator of nitric oxide-dependent cardioprotection 67 . Other work in mice revealed that nitroglycerin-induced calcitonin generelated peptide release is eNOS-dependent, with a greater response in females 69 , and estrogen has been shown to upregulate NOS in neonatal rat cardiomyocytes 70 .…”
Section: Discussionmentioning
confidence: 78%
“…They are divided into subpopulations that vary structurally and functionally to such an extent that it is possible to observe distinctions even within the very same tissue, as explained by Hollander et al regarding the categorization of cardiac mitochondria into subsarcolemmal (SSM) and interfibrillar types (IFM) [33]. Furthermore, the notion that mitochondrial metabolism is related both to age and sex has been demonstrated empirically several times based on different levels of sensitivity to Ca 2+ [34], mitochondrial permeability transition pore (mPTP) responsiveness [35] and myocardial protection in IRI [36]. These findings should definitely be considered during the development/evaluation of therapeutic approaches to I/R-linked diseases and surgical procedures.…”
Section: Pathophysiology Of Irimentioning
confidence: 99%
“…Importantly, in a similar study to this one, Casin et al, using another GSNOR inhibitor, N6022, showed similar effects regarding cardioprotection in male mice but not in females [ 47 ]. In fact, in female mice, GSNOR inhibition worsened the damage produced by I–R.…”
Section: Discussionmentioning
confidence: 70%